2022
DOI: 10.1038/s41467-022-29098-7
|View full text |Cite
|
Sign up to set email alerts
|

Cell-intrinsic Aryl Hydrocarbon Receptor signalling is required for the resolution of injury-induced colonic stem cells

Abstract: The aryl hydrocarbon receptor (AHR) is an environmental sensor that integrates microbial and dietary cues to influence physiological processes within the intestinal microenvironment, protecting against colitis and colitis-associated colorectal cancer development. Rapid tissue regeneration upon injury is important for the reinstatement of barrier integrity and its dysregulation promotes malignant transformation. Here we show that AHR is important for the termination of the regenerative response and the reacquis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 90 publications
2
26
0
Order By: Relevance
“…There is increased expression of IFNg at the tissue level, a loss of markers of differentiated cells such as ChgA and Dclk1, as well as an increase in the enterocyte marker Car4. Most notably, Sca-1 protein levels significantly increased in infected epithelial tissue, a notable marker of epithelial damage previously seen in mouse models of colitis (Shah et al, 2022;Yui et al, 2018). Increased Sca-1 expression is also caused during infection by the intestinal parasitic helminth H. polygyrus in an IFNg-dependent manner and is indicative of a reversion to a fetal-like state in tissue (Nusse et al, 2018) .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…There is increased expression of IFNg at the tissue level, a loss of markers of differentiated cells such as ChgA and Dclk1, as well as an increase in the enterocyte marker Car4. Most notably, Sca-1 protein levels significantly increased in infected epithelial tissue, a notable marker of epithelial damage previously seen in mouse models of colitis (Shah et al, 2022;Yui et al, 2018). Increased Sca-1 expression is also caused during infection by the intestinal parasitic helminth H. polygyrus in an IFNg-dependent manner and is indicative of a reversion to a fetal-like state in tissue (Nusse et al, 2018) .…”
Section: Discussionmentioning
confidence: 62%
“…AHR is a transcriptional regulator of genes involved in anti-microbial defence and intestinal epithelial differentiation. It has been shown to play a protective role during colonic bacterial infection and chemically-induced colon damage (Metidji et al, 2018;Shah et al, 2022;Stockinger et al, 2021). To determine whether AHR executes similar disease protective functions in the small intestine, we infected full body AHR knockout (AHRKO Body ) mice with Ct-CR.…”
Section: Haematopoietic Cell Specific Aryl Hydrocarbon Receptor-defic...mentioning
confidence: 99%
“…Inside gastrointestinal tract, epithelium possesses a noticeable ability to self-renewal leading to replenishment of epithelial cells every 3 to 4 days. The mature epithelial cells could efficiently regenerate after any intestinal injury [ 22 ]. In the resting state, AhR inside cytoplasm is linked to a heat shock protein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analyzing mice lacking AhR specifically in IECs demonstrated that dietary-induced AhR signaling prevents intestinal tumorigenesis by inhibiting the Wnt/β-catenin signaling in intestinal stem cells through induction of the transcription of E3 ubiquitin ligases ( 154 ). Furthermore, AhR was shown to be indispensable for the termination of the regenerative response in IECs after an injury ( 161 ). Here, the authors analyzed colonic organoid cultures under specific media conditions that either simulate differentiating or regenerative conditions.…”
Section: The Impact Of Nutrients On the Intestinal Epithelium And Iga...mentioning
confidence: 99%